Educação ecológica para a conservação das plantas carnívoras: um estudo de caso no estado da Paraíba - Silva, Caio Vinícius da (2014)
Carnivorous plants constitute a group of organisms that has well-defined requirements and environmental tolerances, it is recognized as bio-indicators of environmental quality and an important biological control agents of the small animals, possessing the potential educational value driven by the curiosity of the students, facilitating the construction of sensitivity and environmental knowledge. This study sought to use carnivorous plants as didactic instruments for the development of sensitivity, knowledge and environmental action students through environmental education in school. To this end, lectures, workshops, questionnaires, discussions and practical classes with students from regular high school public education were developed. Through studies, it was concluded that the carnivorous plants can be used as a teaching resource facilitator of the assimilation of information related to the local ecosystem, highlighting the importance of popular and scientific knowledge, characterizing and valuing regional habitats and species, encouraging research and dynamizing the teaching and learning process.